Headache medication and the COVID-19 pandemic - MaassenVanDenBrink, Antoinette (J Headache Pain, 2020)
The world is currently dominated by the Corona Virus Disease 2019 (COVID-19) pandemic. Besides the obvious concerns about limitation of virus spread and providing the best possible care to infected patients, a concomitant concern has now arisen in view of a putative link between the use of certain drugs, such as Renin-Angiotensin System (RAS) inhibitors and ibuprofen, and an increased risk for COVID-19 infection. We here discuss this concern in relation to headache treatment and conclude that, based on current evidence, there is no reason to abandon treatment of headache patients with RAS inhibitors or ibuprofen.